2021
DOI: 10.1002/brb3.2310
|View full text |Cite
|
Sign up to set email alerts
|

The effects of working memory training in children revealed by behavioral responses and ERP

Abstract: The authors thank principal Yuan and his colleagues from QuYang No. 4 primary school for their helpful assistance in the process of data collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
(156 reference statements)
0
1
0
Order By: Relevance
“…Our results show that audiovisual working memory training induces a higher amplitude for P300, consistent with the previous findings on working memory training in a single modality [17,20,41]. P300 is a well-established index that reflects working memory updates [20,23].…”
Section: Neural Effects Of Audiovisual N-back Trainingsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results show that audiovisual working memory training induces a higher amplitude for P300, consistent with the previous findings on working memory training in a single modality [17,20,41]. P300 is a well-established index that reflects working memory updates [20,23].…”
Section: Neural Effects Of Audiovisual N-back Trainingsupporting
confidence: 92%
“…Recent studies with ERPs have demonstrated that visual and dual n-back working memory training tasks modulate separate components of the working memory process [17,18]. They found greater N2 amplitudes, which is related to mismatch/match identification [19].…”
Section: Introductionmentioning
confidence: 99%
“…WM training has the potential to produce near transfer effects, but far transfer effects are less common. WM training has been found to be beneficial for students in areas related to language, such as reading comprehension and listening comprehension (Artuso et al, 2019(Artuso et al, ), as 10.3389/feduc.2023 Frontiers in Education 03 frontiersin.org well as in mathematical abilities such as numerical capacities, reasoning, and arithmetic skills (Holmes et al, 2009;Kuhn and Holling, 2014;Söderqvist and Bergman Nutley, 2015), emotion regulation (Xu et al, 2021), attention level (Volckaert and Noël, 2015), and intelligence (Jaeggi et al, 2008). However, a similar volume of research evidence has shown limited or no improvement after training.…”
Section: Can Transfer Effects Be Detected After the Training?mentioning
confidence: 99%